1986
DOI: 10.1113/jphysiol.1986.sp016297
|View full text |Cite
|
Sign up to set email alerts
|

Organization and post‐natal development of the monkey's lateral geniculate nucleus.

Abstract: SUMMARY1. We have studied the properties of neurones in the lateral geniculate nucleus (l.g.n.) of Old World monkeys, both in mature animals and throughout post-natal development.2. Cells were classified as X (linear) or Y (non-linear) on the basis of their responses to contrast-reversing achromatic gratings ('null position test'). In older animals virtually all parvocellular neurones and the majority of magnocellular units were X cells; only about 15 % of magnocellular neurones displayed highly non-linear spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
103
3
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(124 citation statements)
references
References 64 publications
17
103
3
1
Order By: Relevance
“…Visually evoked firing in infants, however, was generally robust and seemed only slightly less vigorous than in adults. It has been reported that the peak firing rate of neurons in the primate LGN is relatively low in young animals and that cells fatigue easily and are generally sluggish (Blakemore and Vital-Durand, 1986;Hawken et al, 1997), but we did not find infant neurons to be especially sluggish or prone to fatigue. Peak evoked firing rates for our cells grew only a little during development-the mean peak modulated rate in 1-week-old animals was 21.3 ips, growing to 26.2 ips at 4 weeks, and 28.4 ips in adults; the median rates followed a similar trend (14.3, 22.3, and 23.1 ips, respectively); M-and P-cells improved at similar rates.…”
Section: Resultscontrasting
confidence: 89%
See 3 more Smart Citations
“…Visually evoked firing in infants, however, was generally robust and seemed only slightly less vigorous than in adults. It has been reported that the peak firing rate of neurons in the primate LGN is relatively low in young animals and that cells fatigue easily and are generally sluggish (Blakemore and Vital-Durand, 1986;Hawken et al, 1997), but we did not find infant neurons to be especially sluggish or prone to fatigue. Peak evoked firing rates for our cells grew only a little during development-the mean peak modulated rate in 1-week-old animals was 21.3 ips, growing to 26.2 ips at 4 weeks, and 28.4 ips in adults; the median rates followed a similar trend (14.3, 22.3, and 23.1 ips, respectively); M-and P-cells improved at similar rates.…”
Section: Resultscontrasting
confidence: 89%
“…The lateral geniculate nucleus (LGN) receives information from all of the major classes of ganglion cells and provides the afferent input to the primary visual cortex. Two previous studies of development in primate LGN suggest a correlation between acuity and contrast sensitivity development, and the maturation of receptive field properties in LGN neurons (Blakemore and Vital-Durand, 1986;Hawken et al, 1997). Blakemore and Vital-Durand (1986) found neurons in infants to be visually responsive, but sluggish, weak, and with a tendency to fatigue.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Cells with similar visual response properties, the Y-cells, were first observed more than forty years ago in the cat retina (Enroth-Cugell and Robson, 1966). The original observation of the cat Y-cells was followed by a decades-long search for the counterpart of these cells both in the primate retina and in the primate lateral geniculate nucleus (LGN) (de Monasterio, 1978;Kaplan and Shapley, 1982;Derrington and Lennie, 1984;Blakemore and Vital-Durand, 1986;Benardete et al, 1992;Levitt et al, 2001;White et al, 2002). Until this report, no clear evidence had been found for a distinct type of Y-like retinal ganglion cell in the primate.…”
Section: Introductionmentioning
confidence: 99%